Evaluación de la función renal y urinaria en perros adultos (jóvenes y geriátricos) - monografía (2020)
There are several techniques that can be used to assess the kidney function of patients, for example, urinalysis that gives us a physical-chemical assessment of urine, and different proteins that are used to estimate the rate of glomerular filtration; among them, we can mention creatinine, Cystatin C, SDMA (symmetrical dimethylarginine), creatinine clearance. In human medicine, the physiological variables between young adults and elderly or geriatric patients are clear, which provides better medical management. On the contrary, this is a topic that in the light of small animal medicine is not well defined yet. Because of this, we proceeded to make an extensive literature review on the difference between renal physiological variables of young adult and geriatric dogs, evidencing that there can be physiological changes in geriatric patients influenced by age but there are still missing experimental studies to corroborate this hypothesis. In addition, the differences in variables found between young adult geriatric dogs are not significant.